Tandem Walking Exercise For The Risk Of Falling and The Daily and Activities’ Independency Toward Elderly Preopleat UPT PSTW Nirwana Puri Samarinda - Widiastuti, Hesti Prawita; Pamungkas, Leny; Arsyawina, Arsyawina; Hilda, Hilda (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Stability is the ability of maintaining static and dynamics equilibrium, which influenced the falling incident and the capability in doing everyday activities of elderliesPurpose: The purpose of this study is to analyze the effect of tandem walking exercise for the daily activities’ independency and the risk of falling towards elderly people.Methods: This research is quasi experiment with pre and post-test nonequivalent control group design. The samples are 22 people that distributed into control and treatment group who were given tandem walking exercise three times a week for two weeks. Assessment of the independence of daily activities through observation, interviews and using barthel index instruments while falling risk is assessed using Time Up and Go Test (TUGT).Results: The result of hypothesis tests with Wilcoxon obtained that there is an impact from tandem walking exercise for the daily activities’ independency (p value = 0,009) and the risk of falling (p value = 0,003). The deviation analysis on two groups acquired that the Group 1 with interventions of tandem walking exercise is having more impact on the improvement of daily activities’ independency with Mann-Whitney test (p value = 0,044) and the reduction on risk of falling with Independent T-Test (p value = 0,000) compared to Control Group.Conclusion: Tandem walking exercise could improve daily activities’ independency and lower the risk of falling towards elderly people